Quasi-concave (composition) functions with nonconcave argument functions - Fabella, Raul V. (International Economic Review)
The concavity assumption in the known composition mapping result may be too restrictive for certain applications in the household production model and trade theory. The author shows how quasi-concave composition functions are generated when among the arguments are nonconcave, but still quasi-concave, functions. Copyright 1992 by Economics Department of the University of Pennsylvania and the Osaka University Institute of Social and Economic Research Association.